Self-Evisceration of Intestines as the Initial Presentation of Schizoaffective Disorder - Stephanie Hamlin; Dana L. Sharma; Anita S. Kablinger (Case Reports in Psychiatry)
Schizoaffective disorder is categorized by major mood episodes and symptoms of schizophrenia that include disorganized speech, delusions, paranoia, and hallucinations. It is associated with risk factors, including a history of abuse and cannabis use, and patients are typically diagnosed in adolescence and young adulthood. In this case report, we describe the unusual case of a 39-year-old male patient with undiagnosed schizoaffective disorder who self-eviscerated his intestines during an episode of psychosis. He received an emergent exploratory laparotomy with a partial colectomy. After medical stabilization and reorientation, the patient recalled a 10-year history of paranoia associated with significant cannabis use, despite otherwise functioning appropriately in society. During a two-week hospital course, his paranoia and hallucinations were remitted on olanzapine and valproic acid. In addition to discussing his presentation and recollection of the incident, we also discuss similar cases of self-mutilation in nonsuicidal patients and the relationship between cannabis use and schizophrenia spectrum disorders.